Systematic Literature Review Tahun 2019-2021: Kebijakan Pengembangan Pariwisata Asia, Eropa, dan Amerika - Oktaviruzan Azis Hastomi; Rutiana Dwi Wahyunengseh (Jurnal Mahasiswa Wacana Publik, 2022)
The COVID-19 pandemic has created very significant new changes in the global tourism industry. This has implications for the freedom of tourists to enjoy the tourism industry. The existence of this pandemic requires tourism industry players to adapt and innovate according to current conditions. So specifically, this study aims to find out how the direction of tourism development policies carried out by countries in the world, especially in Asia, Europe, and America, which was photographed in the research from 2019 to 2021. The method used in this study is Systematic Literature Review (SLR), using the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) research protocol. Article screening was carried out by reading the title, abstract, keywords and full text using predetermined inclusion and exclusion criteria, which were then assessed using JBI Critical Appraisal Tools, based on an assessment of research journals using 22 articles used in this paper. The results of the study indicate that the direction of tourism development policies in several Asian and European countries is relatively the same where both are developing cultural tourism and green tourism while in several countries in the american they are developing sustainable tourism.